Alterações fisiológicas de gramíneas tropicais submetidas a diferentes níveis de irradiância - Silva, Laudson Ferreira da (2017)
This work aimed to analyze the growth and the partition of assimilates in plants such as Urochloa brizantha cv. Marandu, U. decumbens cv. Basilisk, Panicum maximum cv. Massai and Cynodon dactylon cv. Vaquero, submitted to three levels of luminosity (100, 50 and 25%). The plants were collected at regular intervals of seven days, from the 20th day after the emergency (DAE), to seventy six DAE, with a last collection of ninety DAE. The height (H), tiller number (TN), root dry matter (RDM), stem dry matter (SDM), leaf dry matter (LDM), leaf mass ratio (LMR), ratio between root dry matter and aerial part of the dry matter (RRAP), total dry matter (TDM), specific leaf area (SLA), leaf area ratio (LAR), liquid assimilation rate (LIAR), relative growth rate (RGR), leaf area index (LAI), crop growth rate (CGR), chlorophyll and carotenoids content. The analyzed species grew and developed in an environment with 50% of light equivalent to plants grown in full sun, since there were no significant differences regarding H, RDM, SDM, LDMC, TDM. Similarly, there was no significant difference in LIAR, RGR and CGR in the species, except in P. maximum, which presented such physiological indicators of growth higher than plants grown in the full sun. LAI was also equivalent, except for U. brizantha and U. decumbens, which presented higher index than plants in full sun. The luminosity level of 25% negatively affected the growth and development of the species, except in P. maximum, whose results were equivalent to those presented in full sun and 50% of light. Species demonstrate tolerance to light restriction and, therefore, production potential to be used in silvopasture and agrosilvopasture production systems.